Analysis of indexes of Kazakhstan higher education accessibility - Konopyanova, G.A.; Baikenov, Zh.E.; Brauweiler, Ch. (BUKETOV BUSINESS REVIEW, 2018)
Development of higher education ordinarily indicates the level of development of the country as a whole. This also refers to the accessibility of higher education, which is taken into account in the calculation of many world indexes that characterize the development of a particular state in the world ranking. The accessibility of higher education is one of the priorities for the development of higher education in Kazakhstan in accordance with the State Program for the Development of Education and Science for 2016–2019. The accessibility of higher education depends on many factors, including the standard of living of the population, tuition fees, financing of education by the state, the availability of various mechanisms for admission to higher education institutions. The article analyzes the accessibility of higher education in Kazakhstan, which results in drawing a conclusion that it is necessary to strengthen integration processes in the field of higher education aimed at improving the level of accessibility of education in higher education institutions of the country.